Express System of Trans Operative Determination of the Viability of Biological Tissue and Devices for its Implementation - A.V, Berdnikov; D.I, Voroshnin; I.S, Malkov; D.Kh, Misiev; N.M, Nazmutdinova; N.A, Yunusov (International Journal of Engineering and Technology, 2018)
The article solves the problem of increasing the objectivity of the visual analysis of internal organs during surgery. As a result of the analysis, the authors found that spectral research in the visible spectrum and in the field of infrared radiation allows the practicing surgeon to determine the presence of pathologies of internal organs, as well as the location of their boundaries. At the same time, the use of the infrared range allows one to abstract from the color of the biological tissue to obtain information about the structure of its surface, while the applied HSV color model allows for research in the visible spectrum with conversion of dominant reflected radiation into wavelengths.Â Â